Intelligent Optimization of Parameters for Tens of MA-Class Z-Pinch Accelerators. (19th August 2022) - Fan, Siyuan; Wei, Hao; Gong, Zhenzhou; He, Xu; Sun, Fengju; Qiu, Aici
Abstract : In order to minimize the initial energy storage of tens of MA-class Z- pinch accelerators, an intelligent optimization method was developed based on the transmission line code circuit model and PSOGSA algorithm. Using several input parameters, the four overall parameters of the Z- pinch accelerator could be fast determined, including the connection and parallel combination of LTD cavities, the outer radius of the stack-MITL system, and electrical length of monolithic radial transmission lines. The optimization method has been verified by comparing the results with the Z -300 and Z -800 conceptual designs. By means of this intelligent optimization, some factors that affect the initial energy storage on high-current Z -pinch accelerators have been investigated, such as the operating electrical fields, the diameter of the stack-MITL system, and the inner diameter of the LTD cavity. The suggestions for designing relatively low-cost, efficient LTD-based accelerators have been proposed.